External Parasites of Sheep and Goats - Phillip E. Kaufman; Philip G. Koehler; Jerry F. Butler (EDIS, 2006)
Arthropod pests limit production in the sheep and goat industry in many ways. External parasites feed on body tissue such as blood, skin, and hair. The wounds and skin irritation produced by these parasites result in discomfort and irritation to the animal. Parasites can transmit diseases from sick to healthy animals. They can reduce weight gains and milk production. In general, infested livestock cannot be efficiently managed to realize optimum production levels.  This document is ENY-273 (IG129), one of a series of the Department of Entomology and Nematology, UF/IFAS Extension. Original publication date July 1993. Revised March 2006.